Eligibility Study on Floating Solar Panel Installation over Brackish Water in Sungsang, South Sumatra - Sasmanto, Andri Agus; Dewi, Tresna; Rusdianasari (EMITTER International Journal of Engineering Technology, 2020)
Electric generation using the photovoltaic (PV) effect is considered ideal in South Sumatra as a response to the government policy to increase the utilization of renewable energy to support the depletion of conventional energy. PV panels can be installed in a fishing village in the Sungsang Estuary. This paper examined the eligibility analysis for the installation of PV panels on brackish water. In this research, two Panels are installed, the first one is floating over a water body, and the second is ground mounted as a comparison of electricity produced and efficiency. The Jsc floating and ground mounting differ in 0.4435 A. The measured Jload in floating PV panels is 0.3900 A higher than the ground mounting. The measured Voc at the floating PV panels is 0.2935 V higher, and the Vload of the floating PV panel is 3.0742 V higher than the ground mount. The differences are due to the floating PV panel surface temperature being lower than ground mounting. Electricity generated by floating PV panels is averagely 11.89 Watt higher, and the efficiency is 4% higher than that of ground installation. This experiment also shows that PV panels can be installed over brackish water in the fishing village of Sungsang Estuary.